Trends and Determinants of Child Growth Indicators in Malawi and Implications for the Sustainable Development Goals - Henry V. Doctor; Sangwani Nkhana-Salimu (AIMS Press, 2017)
Sustainable development goals (SGD) 2 links malnutrition, morbidity and child mortality to stunting, wasting and overweight among children under-5 years of age. Sub-Saharan Africa still registers high nutritionally insecure people. In particular, Malawi has made modest progress in improving nutritional outcomes; and still experiences a number of structural challenges leading to negative nutritional outcomes. We describe trends of under nutrition and how the effect of selected determinants of child nutrition affect Malawian children under-5 from 1992 to 2015-16; and examine the changing patterns of the effect of selected socio-demographic characteristics on stunting and underweight using data from demographic and health surveys (DHS). The analysis included 31,630 children under-5 years from 1992, 2000, 2004, 2010, and 2015-16 DHS. Our outcome measures are stunting (height/length-for-age) and underweight (weight-for-age) less than -2 SD (Z-score). We perform logistic regression to assess the relationship between selected socio-demographic characteristics with the stunting and underweight variables. Underweight decreased by 14.0% from 24.7% (1992) to 10.7% (2015-16). Stunting decreased by 23.0% from 55.6% (1992) to 32.6% (2015-16). Underweight was more prevalent among children from central and southern regions; among male children; and children above 6 months of age or more. Later surveys were associated with reduced likelihood of underweight than the earliest surveys. Similar trends were observed between socioeconomic factors and stunting. The observed underweight and stunting prevalence is 2.2% and 1.9% lower than expected, respectively. Despite modest declines in underweight and stunting among young children in Malawi, underweight and stunting remain significant public health challenges particularly in southern and central Malawi which constitute about 85% of the total population. Interventions to address the critical malnutrition challenges in Malawi are inevitable within the context of SDG 2 on health.